Memahami Pengalaman Body Shaming Pada Selebriti Instagram: (Studi Fenomenologi Selebriti Agiskakhansa) - Trimilda Shopiyah, Annur; Murtiadi, Murtiadi; Al Paksi, Yudha Febri (Brand Communication, 2023)
The concept of ideal standardization is raised by the physical variations present in each individual. The purpose of this study is to comprehend the experiences of Instagram celebrities who have been subjected to body-shaming. A phenomenological approach and descriptive qualitative research techniques are used in this study. In contrast, phenomenology bases its understanding of the universe on direct experience. The focus of this study is a person named Agiskakhansa, an Instagram star who has endured body shaming from both his followers and peers. In this study, observation, interviews, and documentation were used as data collection methods. The strategy for processing and analyzing data employed is to gather all the information from the notes and evaluate it using logical words that are appropriate for the environment and circumstances in the field, including interviews, observations, and documentation. The findings of this study demonstrate that bodyshaming behavior should not be dismissed as insignificant because it will have an adverse psychological effect on the victim, leading to feelings of insecurity, dread, and even self-harm. Because of this, society must deal decisively with instances of body shaming.